Italian fascism's forgotten LGBT victims : asylums and internment, 1922-1943 - Romano, Gabriella, 1960- 1960- (Bloomsbury Academic, 2024)
"This book examines the question of the repression of LGBT people through psychiatry during the fascist regime in Italy, a subject that has not been investigated until now. It draws together the substantial archival record of patients, doctors and fascist authorities to reconstruct intricate behind-the-scenes dialogue, and to document one of the ways in which the regime repressed LGBT lives in this period. Italian Fascism's Forgotten LGBT Victims focusses on three different institutions in three parts of the country - Rome, Florence and Girifalco, areas with different attitudes and therapeutic approaches. Archive research results are contextualised within the psychiatric theory of the time, highlighting the existing discrepancies between theory and daily routine practice of mental health institutions in Italy during the regime. Until now, scholars of psychiatry have mainly engaged with the late-19th and early-20th century, or the 1970s and 1980s, when asylums were abolished in Italy after the so-called 'Basaglia Law'. Gabriella Romano expands current knowledge of the history of Italian psychiatry and - by analysing the relationship between central government, local authorities and asylum directors - gives new insights into the power relationship between central government and localities. Furthermore, she sheds light on historiography on homosexuality in Italy, a subject that has been largely ignored with regard to the fascist period and more generally."